PATCH GINGIVA MUKOADESIF Î²-CAROTENE SEBAGAI PENCEGAH EFEK SAMPING PAPARAN RADIASI RADIOGRAFI PANORAMIK (Kajian in vivo pada Kelinci galur New Zealand) - , Rurie Ratna Shantiningsih, Prof. Dr. drg. Munakhir Mudjosemedi, SU., Sp.RKG(K), Dr. Med. dr. Indwiani Astuti, Prof. Dr. Suwaldi, M.Sc., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Micronucleus is one of early markers of DNA damage due to panoramic radiography radiation exposure which might be related to carcinogenesis mechanism. The DNA damage occured because of oxidative reaction that can be detected using 8-oxo-dG expression. Î²-Carotene is lipid soluble antioxidant substance which is expected to prevent the oxidative reaction and to improve the juctional communication which detected by Cx-43. The objectives of this study were to prepare and to develop topical Î²-Carotene in order to prevent micronucleus formation on the gingival mucosa due to panoramic radiography exposure. The preparation of Î²-Carotene gingival mucoadhesive patch were done after analizing the Î²-Carotene capability to penetrate gingival mucosa. Î²-Carotene gingival mucoadhesive patch had been applied to gingival mucosa on the experimental rabbits. In Group I, the rabbits werenât applied with the patch. Group II were applied before, Group III just in the time and Group IV after panoramic radiography exposure. Micronucleus samples were taken from the swabbed of rabbitâs gingival mucosa then stained by using modified Feulgen- Rossenbeck. The 8-oxo-dG and Cx-43 expression were detected using immunohistochemistry technique. The results were analyzed using descriptive quantitative analysis, paired t-test, two way anova and Pearson correlation. Î²-Carotene gingival mucoadhesif patch could be formed and the Î²-Carotene substances would be transported into rabbitâs gingival mucosa.The increasing number of micronucleus from Group I had different mean (p<0.05) with Group III and IV. There were significant influences (p<0.05) of Î²-Carotene gingival mucoadhesif patch application on Group II and III. It proved that the application of Î²-Carotene gingival mucoadhesive prevented the increasing number of micronucleus especially when it was applied before and during panoramic radiograpy exposure. In conclusion, the Î²-Carotene gingival mucoadhesive patch can be utilized to prevent the panoramic radiography radiation exposure on rabbitâs gingival mucosa.